Ratio Legis Pengaturan Surat Tanda Registrasi Seumur Hidup Bagi Tenaga Medis - Sekararum, Marissa; Huda, Mokhammad Khoirul; Pramono, Pramono (Jurnal Hukum dan Etika Kesehatan, 2025)
Health is human right and one of the factor of prosperity of country. Doctor and dentist are medical practitioner. Medical practitioner performing medical practice to patient in carrying people’s health. In carrying out medical practice, medical practitioner require a registration certificate. registration certificate valid in five years and must be renewed every five years. The enactment of Law Number 17 of 2023 about Health regulates that registration certificate is permanent. This research aimed to review and determine ratio legis of regulation for permanent registration certificate and the supervision of medical practitioner after permanent registration certificate. The method in this research is a juridical normative research using historical approach, comprataive approach, statue approach, and conceptual approach. The result of this research is permanent registration certificate has positive impact on medical practitioner cause decrease administrative charge and shorter the process. Supervision of medical practice is carried out by the Indonesian Medical Council, government, and organizations. In Law Number 17 of 2023 on health, supervision of medical practice is carried out by the Indonesian Health Council. Keywords : Ratio Legis; Registration Certificate; Medical Practitioner; Supervision.